Activities in English classes inducing positive / negative emotions - Z. Kralova; E. Kovacikova; V. Repova; E. Skorvagova (Russian State Vocational Pedagogical University, 2021)
Introduction. Emotions have been proven to have significant impact on cognitive and motivational aspects of learning. Choosing appropriate activities to stimulate learners' positive emotions can thus greatly promote learning.Aim. The present research is aimed to find out which learning activities induce positive / negative emotions among upper secondary level learners of English as a foreign language and the secondary aim was to identify the emotions experienced.Methodology and research methods. Methodological triangulation applying qualitative research methods (questionnaire, interview and observation) was conducted among 62 learners and their 2 English teachers. A complementary quantitative instrument (scale) was used to detect the subjective emotional comfort of learners during English lessons.Results. The findings revealed prevailing positive habitual comfort of learners and joy as their primary emotion incited mostly by communication activities. Negative emotions of fear and sadness were detected mainly during testing and evaluation.Scientific novelty. The combination of four research methods in a combined research design studying the complex scale of emotions related to learning a foreign language has not been applied yet.Practical significance. Greater understanding of the affective aspect in learning a foreign language which may help foreign language teachers and methodologists select the appropriate activities to effectively address the actual cognitive and affective needs of learners.